Pengaruh Electronic Word Of Mouth Dan Brand Image Terhadap Keputusan Pembelian Kembali Melalui Kepercayaan Pada E-Commerce Shopee (Studi Kasus Pada Gen Z Di Kota Malang) - Muh Bintang Roziq; Siti Asiyah; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the effect of electronic word of mouth (e-WOM) and brand image on repurchase decisions through trust in the Shopee e-commerce platform. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to respondents who had previously made purchases on Shopee. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to examine the relationships among variables. The results indicate that brand image has a significant effect on trust and repurchase decisions. Trust also has a significant effect on repurchase decisions. However, electronic word of mouth does not have a significant effect on trust nor on repurchase decisions through trust. These findings suggest that although the reviews available on Shopee tend to be positive, consumers rely more on personal experience and brand perception in forming trust and making repeat purchase decisions. In conclusion, brand image and trust are the main factors influencing repurchase decisions on the Shopee e-commerce platform, while e-WOM does not directly affect repurchase decisions through trust. Therefore, companies should strengthen their brand image and maintain service quality to enhance customer loyalty. Keywords: Electronic Word Of Mouth, Brand Image, Trust, Repurchase Decision, Shopee